The Biblical ḥerem : a window on Israel's religious experience - Stern, Philip D. (Brown Judaic studies, 2020)
"A groundbreaking, and controversial, examination of the herem, a biblical mode of declaring something (objects, people, cities) proscribed. Stern here reconstructs how the herem relates to other modes of thinking, in the Hebrew Bible and elsewhere in the Ancient Near East."--Provided by publisher